Faktor Yang Mempengaruhi Perilaku Penyedia Makanan Terhadap Pelaksanaan Perilaku Hidup Bersih Dan Sehat Di Warung Kecamatan Panyabungan - Sihombing, Cipto Marianto; Efendy, Ismail; Hadi, Anto Jamma (Window of Health : Jurnal Kesehatan, 2020)
Decreasing the implementation of clean and healthy live behavior is caused by factors of knowledge, attitude, personal hygiene, clean water facilities, and cleanliness of food equipment, as well as waste management facilities. The purpose of this study was to analyze the factors that influence the behavior of food providers towards the implementation of clean and healthy life behavior in the stalls of Panyabungan District, Mandailing Natal District. This research is a survey with cross sectional approach. The population in this study are all stalls that provide food, as many as 50 stalls. The number of samples in this study were 50 stalls with a total sampling technique. Data collection was carried out using a questionnaire. Data analysis was performed with univariate, bivariate (chi square test), and multivariate analysis (logistic regression tests). The results showed that low knowledge as much as 52.0% with p value = 0.003 and OR 22.360, bad attitude as much as 56.0% with p value = 0.034 and OR 3.114, bad personal hygiene as much as 70.0% with p value = 0.002 and OR 11.440, clean water facilities did not meet the requirements as much as 66.0% with a value of p = 0.036 and OR 9.067, poor food equipment hygiene as much as 66.0% with a value of p = 0.007, and the majority of waste management facilities did not meet the requirements as much as 62.0% with a value of p = 0.238 and OR 9,202. The conclusion of this study is that there is a relationship of knowledge, attitudes, personal hygiene, clean water facilities, and cleanliness of food equipment with the implementation of clean and healthy life behaviors. The most dominant variable influencing the behavior of food providers is knowledge. Health workers are expected to hold counseling and health promotion regarding clean and healthy life behavior.